A razão neoliberal de Estado: uma investigação da deturpação neoliberal da Constituição democrática de 1988 pela via de emendas supostamente constitucionais - Leandro de Oliveira Batista (2022)
In Brazil, the Rule of Law was formalized in 1988 with the Constitution enactment, which marks a period of political transition unprecedented in the country's history. The legal system, as well as the aspirations brought by a Constitution marked by the appreciation of human dignity, inaugurates a new era and sets in motion a country that was committed to rebalancing political, economic and social tensions which constituted the historical formation of the country. This research aims to expose the mismatch between the aspirations arranged in the 1988 Constitution and the functioning of a neoliberal Reason of State that legitimizes the distortion of the Constituent Power of the people by implementing a second Constitution disguised through amendments and (un)constitutional interpretations, which were implemented so the market could maintain the appearance of a capable of self-regulation entity in an extremely strategic state for global politics with a peripheral economy and marked by the exercise of deeply conflicting domestic political powers and paradoxically adaptable to the majority of the occasion. In order to do so, the historical thread that runs through the following events is resumed: (I) the post-Weimar Republic tragedy and the warning signal given by the German response to the 1929 economic crisis; (II) the limits of capitalism and the fire alarm sounded by Margaret Thatcher and Ronald Reagan; (III) the atomic siren triggered after the 2008 financial crisis and the political horizon that reveals the Brazilian perspective in a world marked by the new nuclear war and economic intensification.